A hybrid composite of gold and graphene oxide as a PCR enhancer. Issue 113 (30th October 2015) - Jeong, Ha Young; Baek, Seung Hun; Chang, Sung-Jin; Yang, MinHo; Lee, Seok Jae; Lee, Kyoung G.; Park, Tae Jung
Abstract : A hybrid composite of Au/GO was synthesized and its capability as a PCR enhancer was demonstrated. Abstract : A hybrid composite of gold-decorated graphene oxide (GO) was synthesized and applied as a PCR enhancer. The analysis of the results of PCR demonstrates that the gold and graphene oxide (Au/GO) hybrid composite improves PCR performance. The chemical interaction of the hybrid composite and the PCR components and the potential mechanism behind the hybrid composite-assisted PCR were also investigated and discussed.